Analysis of The Common Size Method in Assessing The Financial Performance of Indonesian Syariah Bank - Rizky Ramadhan Pratama; Neri Susati; Kamelia Astuty (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the financial statement structure of Bank Syariah Indonesia using the common size method. The method used in this study is quantitative, examining the financial performance of Bank Syariah Indonesia after analyzing its financial statements using the common size method, with profitability ratios measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The results of the common size analysis of Bank Syariah Indonesia's balance sheet for the 2022–2025 period indicate that the bank's total assets showed significant growth from approximately IDR 305.73 trillion in 2022 to approximately IDR 456 trillion in 2025, indicating strong business expansion through increased financing and customer fundraising. In the asset structure, murabahah receivables and ijarah lease receivables remain dominant, although their percentages have decreased from 40.83% and 39.50% in 2022 to 32.73% and 31.77% in 2025, indicating the diversification of Islamic financing into other instruments as a source of bank asset growth. Meanwhile, based on the profit/loss statement and profitability ratio analysis, Bank Syariah Indonesia demonstrated a consistent and solid performance growth trend during 2022–2025, with fund management income as mudharib and other operating income increasing sharply from 2022 to 2025. A common-size analysis also shows that although third-party profit-sharing rights increased during this period, the contribution of the bank's own profit-sharing rights remained significant, while profitability ratios such as ROA, ROE, and NPM generally increased or remained healthy, reflecting operational efficiency, the bank's ability to utilize assets, and its effectiveness in generating net profit relative to equity during the period.